Characteristic of thyroid carcinoma based on age, sex and histology type at Sanglah General Hospital, Bali, Indonesia, 2016 - Kishan Arrumugam; Ni Putu Ekawati; I Made Gotra (DiscoverSys Inc., 2018)
Background: Thyroid cancer is one of the most common malignancies in the endocrine system whereas the annual mortality rate is increasing each year in Indonesia. This study aims to determine characteristic of thyroid carcinoma based on age, sex, and histology type at Sanglah General Hospital, Bali, Indonesia, 2016.Methods: A cross-sectional study was carried out among 84 patients with thyroid carcinoma at Sanglah General Hospital during January-December 2016. Data were analyzed using secondary data from medical record based on age, sex, and histology type by SPSS ver. 16.Results: The highest prevalence of thyroid carcinoma based on age was found in the 50-54 years group (17.86%). Females were predominant that attributed to 73.8% compared with males (26.2%). In addition, papillary thyroid carcinoma has the highest prevalence in both sexes that is 75% among other types.Conclusion: A 50-54 years-age group, females, and papillary thyroid carcinoma types were predominant at Sanglah General Hospital in 2016.